Clinical characteristics and risk factors for complications of candidaemia in adults: Focus on endophthalmitis, endocarditis, and osteoarticular infections. (April 2020) - Shin, Sung Un; Yu, Yo han; Kim, Soo Sung; Oh, Tae Hoon; Kim, Seong Eun; Kim, Uh Jin; Kang, Seung-Ji; Jang, Hee-Chang; Park, Kyung-Hwa; Jung, Sook In
Highlights: Complications occurred in 4.4% of adults with candidaemia. C . albicans was an independent risk factor for complicated candidaemia in adults. Complications of candidaemia might need prolonged treatment and additional procedures or surgery. Abstract: Objectives: This study evaluated the incidence, risk factors, and clinical characteristics of complications of candidaemia in adults, with a focus on endophthalmitis, endocarditis, and osteoarticular infections. Methods: All patients ≥18 years old with candidaemia in two Korean tertiary hospitals from 2007 to 2016 were investigated. Complications of candidaemia were defined as the presence of endophthalmitis, endocarditis, or osteoarticular infections documented in patients with candidaemia. The clinical characteristics and risk factors for candidaemia with complications were analysed in the patients who underwent ophthalmological examinations. Results: Of 765 adult patients with candidaemia, 34 (4.4%) met the definition of complications, including endophthalmitis in 29 (3.8%), endocarditis in 4 (0.5%), and osteoarticular infections in 3 (0.4%). Of the 225 patients who underwent ophthalmological examinations, 29 (12.9%) had endophthalmitis. Candida albicans was an independent risk factor for complicated candidaemia (OR, 5.12; 95% CI, 2.17–12.09; P < 0.001). Although the mortality rate was no higher in complicated candidaemia, the duration of antifungal therapy was longer (23.1 ± 17.6 vs . 16.4 ± 10.8 days, P = 0.042), and 13 patients (39.3%) underwent additional procedures or surgery. Conclusions: Complications of candidaemia occurred in 4.4% of adult patients. C . albicans was an independent risk factor for complicated candidaemia in adults. Complications of candidaemia might need prolonged treatment and additional procedures or surgery. Therefore, careful evaluation and active treatment of candidaemia with complications should be encouraged.